2011
DOI: 10.1021/ef2007276
|View full text |Cite
|
Sign up to set email alerts
|

Nascent Biomass Tar Evolution Properties under Homogeneous/Heterogeneous Decomposition Conditions in a Two-Stage Reactor

Abstract: In order to study the mechanism of biomass tar formation and elimination in a two-stage downdraft gasifier, the nascent rice straw pyrolysis tar evolution properties under homogeneous/heterogeneous decomposition conditions have been investigated in a constructed lab-scale two-stage reactor by varying factors as temperature, concentration and reforming agents of CO 2 /H 2 O/O 2 , and char bed heights. The nascent tar was produced in the first stage reactor and then decomposed in the second stage with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The yields of H 2 showed no significant differences in tests 4−12, which indicated that water was the dominant factor of the H 2 yield. Wu et al 32 also found that steam showed the highest efficiency in tar elimination, while the presence of CO 2 and O 2 induced the formation of OH, H, and O which promoted hydrocarbon conversion.…”
Section: Effects Of Syngas Components On the Conversionmentioning
confidence: 97%
“…The yields of H 2 showed no significant differences in tests 4−12, which indicated that water was the dominant factor of the H 2 yield. Wu et al 32 also found that steam showed the highest efficiency in tar elimination, while the presence of CO 2 and O 2 induced the formation of OH, H, and O which promoted hydrocarbon conversion.…”
Section: Effects Of Syngas Components On the Conversionmentioning
confidence: 97%
“…The liquid products derived from biomass pyrolysis were determined by weighing, mainly including tar and water [30]. Biomass tar is a complex organic mixture composed of hundreds of condensable hydrocarbon compounds with other oxygenated hydrocarbons, which is determined by weighing [31].…”
Section: Sampling and Analysismentioning
confidence: 99%
“…In the reforming zone, the homogeneous partial oxidation and heterogeneous char conversion are two significant factors to ensure that the low-tar syngas is achieved. The selectively properties of RHC Ni in eliminating tertiary tars greatly increased the application prospects of the gasifier [30]. In this work, the major tar compounds came from tar Class 4; sometimes referred as tertiary tars containing non-oxygenated organic compounds with light PAHs.…”
Section: Gc-ms Analysis Of the Condensed Tarmentioning
confidence: 99%
“…However, phenol was not detected in this study, which can probably be attributed to the relative longer residence time. The aggravation of the pyrolysis process, such as increasing temperature or extended reaction time, was able to remove the oxygen functionalities completely. , The primary reaction of thermal decomposition of phenol is proven to be the production of CPD and CO through: Once CPD forms, it dissociates unimolecularly to the cyclopentadienyl (CPDyl) radical: Two CPDyl radicals combine and rearrange to form naphthalene: Similar to the naphthalene formation process, a phenanthrene can also be formed based on the combination of CPDyl with indenyl (R1072). Therefore, large aromatics can originate from these resonance stabilized radicals.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The aggravation of the pyrolysis process, such as increasing temperature or extended reaction time, was able to remove the oxygen functionalities completely. 6,46 The primary reaction of thermal decomposition of phenol is proven to be the production of CPD and CO through: 47 (R764)…”
Section: Energy and Fuelsmentioning
confidence: 99%